High-strength and high-toughness seamless oil casing and preparation method thereof
By preparing the oil casing substrate and combining it with silanized nano-suspension and modified epoxy resin treatment, the problems of decreased toughness and weak coating adhesion of seamless oil casing after strength improvement were solved, and a seamless oil casing with high strength, toughness and corrosion resistance was realized.
Patent Information
- Application Number
- CN202510999545.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2025-10-28
AI Technical Summary
While existing seamless oil casings improve strength, their toughness decreases, making them prone to brittle fracture. Furthermore, their mechanical properties deteriorate in corrosive environments, the coating has weak adhesion to the substrate, and their corrosion protection is inadequate.
The oil casing substrate is prepared by melting, casting, hot rolling, quenching and double tempering. Combined with silanized nano-suspension treatment and modified epoxy resin spraying, the adhesion between the substrate and the coating is enhanced, and the corrosion resistance and mechanical properties are improved.
It improves the overall performance of seamless oil casing, enhances the adhesion between the coating and the substrate, extends the service life, improves mechanical strength and toughness, and enhances corrosion resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of oil casing manufacturing technology, specifically, it relates to a high-strength and high-toughness seamless oil casing and its preparation method. Background Technology
[0002] With the rapid development of the petroleum industry, my country's demand for high-performance oil casing and tubing is increasing. As a key component in oil and gas extraction, oil casing and tubing must possess high strength, high toughness, excellent corrosion resistance, and wear resistance to withstand complex tensile, compressive, torsional, and bending loads under complex downhole conditions. However, while increasing strength, traditional seamless oil casing and tubing often results in a decrease in toughness, leading to an increased risk of early cracking and fracture, especially in deep wells, ultra-deep wells, and corrosive environments. In high-humidity, high-salt environments such as coastal and offshore oil fields, traditional seamless oil casing and tubing are prone to surface corrosion, resulting in a significant decrease in strength and plasticity, a substantial reduction in service life, severely impacting oil and gas extraction efficiency, and increasing maintenance and replacement costs. Research shows that adding chromium can effectively improve the hardness and corrosion resistance of seamless oil casing and tubing, but excessively high chromium content sacrifices the material's toughness, making it difficult to meet the stringent requirements of high-strength, high-toughness seamless oil casing and tubing for deep well extraction. Therefore, developing a seamless oil casing with high strength, high toughness, good corrosion resistance, and excellent processing performance is of great significance for ensuring the efficient, safe, green, and sustainable development of oil and gas fields.
[0003] While existing technologies can improve the strength of seamless oil casing through alloying and heat treatment, this often leads to a decrease in toughness, especially at high strength levels, where the material is more prone to brittle fracture, affecting its service safety. Furthermore, in environments containing corrosive media (such as H2S, Cl-), the toughness often decreases. - In complex oil and gas environments (such as oil and gas), traditional seamless oil casing is prone to electrochemical corrosion, stress corrosion, etc., which leads to a decline in its mechanical properties and a significant shortening of its service life. Coating the surface of seamless oil casing with epoxy resin or other materials to improve its corrosion resistance is not ideal because the interfacial bonding force between the coating and the metal substrate is weak. The coating is prone to peeling off or cracking from the substrate surface, which seriously affects the anti-corrosion effect and service life of the anti-corrosion coating. Summary of the Invention
[0004] The purpose of this invention is to provide a high-strength and high-toughness seamless oil casing and its preparation method. The method involves melting the raw materials in step S1, casting them into a rod-shaped continuous casting billet, followed by piercing, hot rolling, quenching, and double tempering to obtain the oil casing substrate. The oil casing substrate from step S2 is then treated with a silanized nano-suspension to obtain a pretreated oil casing substrate. Modified epoxy resin is sprayed onto the surface of the pretreated oil casing substrate from step S3, and after curing, a high-strength and high-toughness seamless oil casing is finally obtained. Quenching and double tempering significantly improve the strength and toughness of the seamless oil casing. Treatment of the oil casing substrate with the silanized nano-suspension enhances the adhesion between the modified epoxy resin and the oil casing substrate. The modified epoxy resin significantly improves the corrosion resistance, thermal stability, and mechanical properties of the seamless oil casing, extending its service life and overall improving its comprehensive performance.
[0005] The technical problem this invention aims to solve is as follows: While existing technologies can improve the strength of seamless oil casing through alloying and heat treatment, this often leads to a decrease in toughness, especially at high strength levels, where the material is more prone to brittle fracture, affecting its service safety. Furthermore, in environments containing corrosive media (such as H2S, Cl-), the toughness of the casing is often reduced. - In complex oil and gas environments (such as oil and gas), traditional seamless oil casing is prone to electrochemical corrosion, stress corrosion, etc., which leads to a decline in its mechanical properties and a significant shortening of its service life. Coating the surface of seamless oil casing with epoxy resin or other materials to improve its corrosion resistance is not ideal because the interfacial bonding force between the coating and the metal substrate is weak. The coating is prone to peeling off or cracking from the substrate surface, which seriously affects the anti-corrosion effect and service life of the anti-corrosion coating.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a high-strength and high-toughness seamless oil casing includes the following steps: S1: Raw materials: By weight percentage, it includes the following components: carbon 0.12-0.18%, silicon 0.2-0.4%, manganese 0.6-0.8%, chromium 10-12%, molybdenum 2.5-3.5%, aluminum 0.02-0.04%, phosphorus 0.005-0.01%, zirconium 0.2-0.24%, cerium 0.004-0.006%, yttrium 0.003-0.005%, with the balance being iron and other unavoidable impurities; S2: Preparation of oil casing substrate: The raw materials in step S1 are melted to obtain molten steel. The molten steel is cast into a rod-shaped continuous casting billet, and then pierced and hot rolled to obtain a tube blank. The tube blank is quenched and double tempered to obtain the oil casing substrate. S3: Pre-treatment of the oil casing substrate: The oil casing substrate in step S2 is treated with a silanized nano suspension to obtain a pre-treated oil casing substrate; S4: Preparation of high-strength and toughness seamless oil casing: The modified epoxy resin is sprayed onto the surface of the pretreated oil casing substrate in step S3, and then cured to obtain a high-strength and toughness seamless oil casing. The modified epoxy resin is prepared by functionalizing nanofibers and imide-modified epoxy resin.
[0007] Further, in step S2, the melting process specifically includes: The raw materials in step S1 are smelted in an oxygen-blown converter and fed with rare earth wire. The smelting temperature is 1550-1650℃, and the mass of rare earth wire accounts for 0.02-0.04% of the mass of molten steel. After ladle refining and vacuum degassing, molten steel is obtained.
[0008] Furthermore, the rare earth wire is a Ce wire.
[0009] Furthermore, the ladle refining temperature is 1600-1640℃, and the refining time is 40-60 minutes.
[0010] Furthermore, the vacuum degassing temperature is 1580-1620℃, the vacuum degree is 4-6 Pa, the vacuum degassing time is 20-30 min, and the argon gas flow rate is 120-160 Nm³. 3 / h.
[0011] Furthermore, the piercing and hot rolling process specifically involves heating the bar-shaped continuous casting billet to 1150-1200℃ in a heating furnace and holding it at that temperature for 1.5-2.5 hours. Then, piercing is performed at 1080-1120℃, followed by hot rolling at 900-940℃. After cooling, a tube blank is obtained.
[0012] Furthermore, the quenching process specifically involves: water cooling the tube blank, followed by quenching at a temperature of 890-910℃ and a holding time of 50-70 minutes.
[0013] Furthermore, the double tempering process specifically involves: water cooling after quenching, followed by double tempering. The first tempering temperature is 540-560℃, and the tempering holding time is 25-35 minutes. The second tempering temperature is 440-460℃, and the tempering holding time is 110-130 minutes. After tempering, the product is air-cooled to obtain the oil casing substrate.
[0014] Furthermore, step S3 specifically includes: The oil casing substrate in step S2 is sandblasted. After sandblasting, it is impregnated with silanized nano suspension for 1-2 hours and finally vacuum dried at 105-115℃ for 1.5-2.5 hours to obtain the pretreated oil casing substrate.
[0015] Furthermore, the sandblasting conditions are as follows: 0.4 mm aluminum oxide particles are used for sandblasting, the compressed air pressure is 0.8-1 MPa, the sandblasting distance is 140-180 mm, the sandblasting angle is 90°, and the surface roughness is controlled to be 90-110 mm.
[0016] Furthermore, the preparation method of the silanized nano suspension includes the following steps: Add the silane coupling agent to a mixed solution of ethanol and deionized water and stir for 15-25 minutes. Then add the nanoparticles and continue stirring. Add the dispersant, stir until homogeneous, and then sonicate to obtain a silanized nano suspension.
[0017] Furthermore, the mass ratio of the silane coupling agent, the mixed solution of ethanol and deionized water, the nanoparticles, and the dispersant is 1.8-2.2:90-110:0.04-0.06:0.04-0.06.
[0018] Furthermore, the silane coupling agent is composed of 3-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane mixed in a mass ratio of 2:1.
[0019] Furthermore, the nanoparticles are composed of hydroxylated multi-walled carbon nanotubes and nano-silica in a mass ratio of 0.7-0.8:0.5-0.6.
[0020] Furthermore, the stirring time is 10-15 minutes.
[0021] Furthermore, the dispersant is polyvinylpyrrolidone.
[0022] Furthermore, the ultrasonic treatment time is 20-30 minutes.
[0023] Furthermore, step S4 specifically includes: The modified epoxy resin is sprayed onto the surface of the pretreated oil casing substrate in step S3, and then cured. After curing, a high-strength and high-toughness seamless oil casing is obtained.
[0024] Furthermore, the coating thickness is 200-300 μm.
[0025] Furthermore, the curing process is as follows: first, cure at 115-125℃ for 0.5-1.5h, then cure at 155-165℃ for 1.5-2.5h, and finally cure at 195-205℃ for 2.5-3.5h.
[0026] Furthermore, the preparation method of the modified epoxy resin includes the following steps: Imide is added to epoxy resin, and then stirred at 115-125℃ for 20-30 minutes. After cooling, functionalized nanofibers are added and stirred. After cooling, curing agent is added and stirred evenly. Finally, vacuum degassing is performed to obtain modified epoxy resin.
[0027] In the above reaction process, functionalized nanofibers, imides and epoxy resins are cross-linked together through hydrogen bonding interactions, and finally modified epoxy resin is obtained.
[0028] Further, the mass ratio of the imide, epoxy resin, functionalized nanofibers, and curing agent is 0.08-0.12:0.9-1.1:0.01-0.03:0.1-0.15.
[0029] Furthermore, the curing agent is 4,4'-diaminodiphenylmethane.
[0030] Furthermore, the stirring temperature is 80-90℃ and the stirring time is 0.5-1h.
[0031] Furthermore, the vacuum degassing temperature is 55-65℃, and the time is 15-25 minutes.
[0032] Furthermore, the preparation method of the functionalized nanofibers includes the following steps: Nanofibers were added to Tris buffer solution and sonicated. Dopamine was then added, and sonication was continued. N-[3-(trimethoxysilyl)propyl]ethylenediamine was then added, and hydrochloric acid solution was added to adjust the pH of the system to 8-9. The mixture was stirred for 4.5-5.5 h. After the reaction was completed, the nanofibers were centrifuged, washed with ethanol and deionized water, and finally vacuum dried to obtain functionalized nanofibers.
[0033] In the above reaction process, dopamine undergoes an oxidative self-polymerization reaction to generate polydopamine, which can be adsorbed on the surface of nanofibers. Then, N-[3-(trimethoxysilyl)propyl]ethylenediamine is hydrolyzed to produce silanol groups, which can react and combine with polydopamine. Thus, N-[3-(trimethoxysilyl)propyl]ethylenediamine and polydopamine are combined on the surface of nanofibers, and finally functionalized nanofibers are obtained.
[0034] Furthermore, the mass ratio of the nanofibers, Tris buffer solution, dopamine, and N-[3-(trimethoxysilyl)propyl]ethylenediamine is 0.1-0.2:140-160:0.05-0.07:0.15-0.25.
[0035] Furthermore, the ultrasonic treatment time is 15-25 minutes.
[0036] Furthermore, the duration of the continued ultrasonic treatment is 15-25 minutes.
[0037] Furthermore, the vacuum drying temperature is 55-65℃, and the time is 24 hours.
[0038] Furthermore, the nanofibers are composed of hexagonal boron nitride nanofibers and carbon nanofibers in a mass ratio of 0.9-1.1:0.6-0.7.
[0039] Furthermore, the preparation method of the hexagonal boron nitride nanofibers includes the following steps: Melamine, boric acid, and deionized water were added to deionized water in a mass ratio of 9.3:6.3:500 and stirred until homogeneous. The mixture was then stirred and reacted at 85°C for 12 hours. Finally, the mixture was heat-treated at 1050°C under a nitrogen atmosphere for 3.5 hours to obtain hexagonal boron nitride nanofibers.
[0040] Furthermore, the method for preparing the imide includes the following steps: Diamine and dianhydride were added to N-methylpyrrolidone and reacted under a nitrogen atmosphere for 11-13 hours. After the reaction was completed, toluene was added and stirred until homogeneous. The mixture was then refluxed and cooled to room temperature. The solution was then poured into a mixture of deionized water and methanol, allowed to stand, centrifuged, washed with deionized water, and finally dried under vacuum to obtain imide.
[0041] Furthermore, the mass ratio of the diamine, dianhydride, N-methylpyrrolidone, and toluene is 1.7-1.9:0.8-1:25-35:15-17.
[0042] Furthermore, the diamine is 4,4'-diaminodiphenyl ether.
[0043] Furthermore, the dianhydride is composed of a mixture of 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4-hexafluoroisopropylphthalic anhydride in a mass ratio of 0.7-0.8:0.4-0.5.
[0044] Furthermore, the reflux reaction is carried out at a temperature of 175-185°C for 8-10 hours.
[0045] Furthermore, the settling time is 1-2 hours.
[0046] Furthermore, the vacuum drying temperature is 60-70℃, and the time is 12 hours.
[0047] A high-strength and high-toughness seamless oil casing prepared by the above-described method.
[0048] The beneficial effects of this invention are: (1) In the technical solution of this invention, the raw materials are melted, then cast into rod-shaped continuous casting billets, and then pierced, hot rolled, quenched and double tempered to obtain the oil casing matrix; the interaction between the raw materials can effectively improve the corrosion resistance, mechanical strength and stability of the seamless oil casing, and the quenching and double tempering treatment can effectively reduce the grain size, thus improving the toughness and mechanical strength of the seamless oil casing; the oil casing matrix is treated with silanized nano suspension to obtain a pretreated oil casing matrix; the silanized nano suspension is prepared by mixing silane coupling agent, dispersant and nanoparticles; the silane coupling agent can The formation of stable covalent bond structures on the surface of nanoparticles facilitates the formation of cross-linked network films between the nanoparticles and the casing substrate. Furthermore, the dispersant in the suspension can significantly improve the dispersion stability of the suspension itself. In addition, the nanoparticles are composed of a mixture of hydroxylated multi-walled carbon nanotubes and nano-silica. The hydroxylated multi-walled carbon nanotubes and nano-silica have a synergistic effect, which can not only increase the interfacial bonding force between the casing substrate and the modified epoxy resin and improve its adhesion, but also further improve the mechanical strength and toughness of the seamless casing, and have a good influence on the corrosion resistance and thermal stability of the seamless casing.
[0049] (2) In the technical solution of the present invention, a high-strength and tough seamless oil casing is obtained by spraying modified epoxy resin onto the surface of a pretreated oil casing substrate and then curing it; the modified epoxy resin is prepared by modifying epoxy resin with functionalized nanofibers and imide; wherein, the functionalized nanofibers are prepared by modifying nanofibers with N-[3-(trimethoxysilyl)propyl]ethylenediamine and polydopamine; polydopamine can be well adsorbed on the surface of nanofibers and then combined with N-[3-(trimethoxysilyl)propyl]ethylenediamine, which can not only improve the corrosion resistance and thermal stability of epoxy resin, but also improve the dispersibility of nanofibers and enhance the interfacial bonding force between them and epoxy resin; the nanofibers are composed of a mixture of hexagonal boron nitride nanofibers and carbon nanofibers, which have a good synergistic effect and can effectively improve the corrosion resistance of epoxy resin. The epoxy resin exhibits improved thermal stability, mechanical properties, and thermal stability. Imidics are prepared by combining diamines and dianhydrides. Adding imides to epoxy resins further enhances their thermal stability and mechanical properties. The dianhydride is composed of a mixture of 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4-hexafluoroisopropylphthalic anhydride. The 1,4,5,8-naphthalenetetracarboxylic anhydride contains a naphthalene ring, resulting in good thermal stability, while the 4,4-hexafluoroisopropylphthalic anhydride contains a trifluoromethyl group, providing good hydrophobicity. The 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4-hexafluoroisopropylphthalic anhydride work synergistically to significantly improve the thermal stability, mechanical strength, and toughness of the epoxy resin, and also have a positive impact on its corrosion resistance. Furthermore, spraying the modified epoxy resin onto the pretreated oil casing substrate surface further enhances the overall performance of the seamless oil casing.
[0050] (3) In the technical solution of the present invention, after the oil casing substrate is treated with silanized nano suspension, modified epoxy resin is sprayed and cured to finally obtain a high-strength and tough seamless oil casing. The obtained high-strength and tough seamless oil casing not only has good mechanical properties, corrosion resistance and thermal stability, but also improves the interfacial adhesion between the coating and the oil casing substrate, improves the protective effect of the coating, and extends the service life of the seamless oil casing. The overall comprehensive performance is good. Detailed Implementation
[0051] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0052] The specific parameters of the raw materials used in this invention are as follows: Hydroxylated multi-walled carbon nanotubes, product number: S33840, provided by Shanghai Yuanye Biotechnology Co., Ltd.; Nano silica, CAS No.: 7631-86-9, product number: A61745, provided by Saen Chemical Technology (Shanghai) Co., Ltd.; Epoxy resin (bisphenol A type epoxy resin), CAS No.: 25085-99-8, provided by Shanghai Yien Chemical Technology Co., Ltd.; Carbon nanofibers, product number: C493384-02, provided by Shanghai Aladdin Biochemical Technology Co., Ltd.; 1,4,5,8-naphthalenetetracarboxylic anhydride, CAS No.: 81-30-1, product number: N107577, provided by Shanghai Aladdin Biochemical Technology Co., Ltd.; 4,4-hexafluoroisopropylphthalic anhydride, CAS No.: 1107-00-2, product number: H810819, provided by Shanghai Maclean Biochemical Technology Co., Ltd.
[0053] The preparation method of hexagonal boron nitride nanofibers includes the following steps: Melamine, boric acid, and deionized water were added to deionized water in a mass ratio of 9.3:6.3:500 and stirred until homogeneous. The mixture was then stirred and reacted at 85°C for 12 hours. Finally, the mixture was heat-treated at 1050°C under a nitrogen atmosphere for 3.5 hours to obtain hexagonal boron nitride nanofibers. Example 1
[0054] The specific steps for preparing modified epoxy resin are as follows: According to the mass ratio of imide, epoxy resin, functionalized nanofibers, and 4,4'-diaminodiphenylmethane being 0.08:0.9:0.01:0.1, imide was added to epoxy resin, and then stirred at 115°C for 30 min. After cooling to 80°C, functionalized nanofibers were added, and the mixture was stirred at 80°C for 1 h. After cooling to 55°C, 4,4'-diaminodiphenylmethane was added, and the mixture was stirred for 30 min. Finally, the mixture was degassed under vacuum at 55°C for 25 min to obtain modified epoxy resin. The preparation method of functionalized nanofibers includes the following steps: Following a mass ratio of nanofibers, Tris buffer solution, dopamine, and N-[3-(trimethoxysilyl)propyl]ethylenediamine of 0.1:140:0.05:0.15, nanofibers were added to 0.01 mol / L Tris buffer solution and sonicated for 15 min (ultrasonic power 100 W, ultrasonic frequency 40 kHz). Dopamine was then added, and sonication was continued for another 15 min (ultrasonic power 100 W, ultrasonic frequency 40 kHz). N-[3-(trimethoxysilyl)propyl]ethylenediamine was then added, and the pH of the system was adjusted to 8 with 0.1 mol / L hydrochloric acid solution. The mixture was stirred for 4.5 h. After the reaction, the mixture was centrifuged at 10000 rpm for 10 min and washed three times each with ethanol and deionized water (each time the ethanol mass was 8% of the Tris buffer solution mass, and each time the deionized water mass was 8% of the Tris buffer solution mass). The buffer solution (10% by mass) was then vacuum dried at 55°C for 24 hours to obtain functionalized nanofibers. The nanofibers were composed of hexagonal boron nitride nanofibers and carbon nanofibers in a mass ratio of 0.9:0.6. The preparation method of imide includes the following steps: The mass ratio of 4,4'-diaminodiphenyl ether, dianhydride, N-methylpyrrolidone, and toluene was 1.7:0.8:25:15. 4,4'-diaminodiphenyl ether and dianhydride were added to N-methylpyrrolidone, and the reaction was carried out under a nitrogen atmosphere at room temperature for 11 hours. After the reaction was complete, toluene was added, and the mixture was stirred thoroughly. The mixture was then refluxed at 175°C for 10 hours. After cooling to room temperature, the mixture was poured into a mixed solution of deionized water and methanol (volume ratio of deionized water to methanol was 1:1). The mass of the deionized water and methanol mixture was twice that of N-methylpyrrolidone. After standing for 1 hour, the mixture was centrifuged at 4000 rpm for 15 minutes, the precipitate was collected, and washed three times with deionized water (each time the mass of deionized water was 50% of the mass of N-methylpyrrolidone). Finally, the mixture was vacuum dried at 60 °C for 12 hours to obtain an imide. The dianhydride in this imide was composed of a mixture of 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4-hexafluoroisopropylphthalic anhydride in a mass ratio of 0.7:0.4. The specific steps for preparing high-strength and high-toughness seamless oil casing are as follows: S1: Raw materials: By weight percentage, it includes the following components: carbon 0.12%, silicon 0.2%, manganese 0.6%, chromium 10%, molybdenum 2.5%, aluminum 0.02%, phosphorus 0.005%, zirconium 0.2%, cerium 0.004%, yttrium 0.003%, with the balance being iron and other unavoidable impurities; S2: Preparation of the oil casing substrate: The raw materials from step S1 are steelled in an oxygen-blown converter and fed with Ce wire. The steelmaking temperature is 1550℃, and the mass of Ce wire accounts for 0.02% of the mass of the molten steel. Then, the mixture is refined outside the ladle (refining temperature is 1600℃, refining time is 60min) and vacuum degassing (vacuum degassing temperature is 1580℃, vacuum degree is 4Pa, vacuum degassing time is 30min, and the argon gas flow rate is 120Nm). 3 The steel is obtained by casting molten steel into a bar-shaped continuous casting billet. The bar-shaped continuous casting billet is heated to 1150℃ in a heating furnace and held for 2.5h. Then, it is pierced at 1080℃ and hot rolled at 900℃. After cooling, a tube blank is obtained. The tube blank is water-cooled and then quenched at 890℃ for 70min. After quenching, it is water-cooled and then double-tempered. The first tempering temperature is 540℃ and the tempering holding time is 35min. The second tempering temperature is 440℃ and the tempering holding time is 130min. After tempering, it is air-cooled to obtain the oil casing base. S3: Pretreatment of the casing substrate: The casing substrate from step S2 is sandblasted. After sandblasting, it is impregnated with a silanized nano-suspension for 1 hour (per cm). 2 The oil casing substrate was treated with 0.1 mL of silanized nano suspension and then vacuum dried at 105 °C for 2.5 h to obtain the pretreated oil casing substrate. The sandblasting conditions were as follows: 0.4 mm alumina particles were selected for sandblasting, the compressed air pressure was 0.8 MPa, the sandblasting distance was 140 mm, the sandblasting angle was 90°, and the surface roughness was controlled at 90 mm. The preparation method of silanized nano-suspension includes the following steps: The silane coupling agent, a mixed solution of ethanol and deionized water, nanoparticles, and polyvinylpyrrolidone were mixed in a mass ratio of 1.8:90:0.04:0.04. The silane coupling agent was added to the mixed solution of ethanol and deionized water (volume ratio of ethanol to deionized water was 9:1), and stirred at 2000 rpm for 15 min at room temperature. Then, the nanoparticles were added, and stirring continued for 10 min. Next, polyvinylpyrrolidone was added, and the mixture was stirred until homogeneous. The mixture was then ultrasonically treated for 20 min (ultrasonic power 100 W, ultrasonic frequency 40 kHz) to obtain a silanized nanoparticle suspension. The silane coupling agent was composed of a mixture of 3-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane in a mass ratio of 2:1; the nanoparticles were composed of a mixture of hydroxylated multi-walled carbon nanotubes and nano-silica in a mass ratio of 0.7:0.5. S4: Preparation of high-strength and toughness seamless oil casing: Modified epoxy resin is sprayed onto the surface of the pretreated oil casing substrate in step S3, and then cured. First, it is cured at 115℃ for 1.5h, then at 155℃ for 2.5h, and finally at 195℃ for 3.5h. After curing, a high-strength and toughness seamless oil casing is obtained, wherein the spraying thickness is 200μm. Example 2
[0055] The specific steps for preparing modified epoxy resin are as follows: According to the mass ratio of imide, epoxy resin, functionalized nanofibers, and 4,4'-diaminodiphenylmethane being 0.1:1:0.02:0.12, imide was added to epoxy resin, and then stirred at 120°C for 25 min. After cooling to 85°C, functionalized nanofibers were added, and the mixture was stirred at 85°C for 0.7 h. After cooling to 60°C, 4,4'-diaminodiphenylmethane was added, and the mixture was stirred for 25 min. Finally, the mixture was degassed under vacuum at 60°C for 20 min to obtain modified epoxy resin. The preparation method of functionalized nanofibers includes the following steps: Following a mass ratio of nanofibers, Tris buffer solution, dopamine, and N-[3-(trimethoxysilyl)propyl]ethylenediamine of 0.15:150:0.06:0.2, nanofibers were added to 0.01 mol / L Tris buffer solution and sonicated for 20 min (ultrasonic power 100 W, ultrasonic frequency 40 kHz). Dopamine was then added, and sonication was continued for another 20 min (ultrasonic power 100 W, ultrasonic frequency 40 kHz). N-[3-(trimethoxysilyl)propyl]ethylenediamine was then added, and the pH of the system was adjusted to 8.5 with 0.1 mol / L hydrochloric acid solution. The mixture was stirred for 5 h. After the reaction, the mixture was centrifuged at 10000 rpm for 12 min and washed three times each with ethanol and deionized water (each time the ethanol mass was 8% of the Tris buffer solution mass, and each time the deionized water mass was 8% of the Tris buffer solution mass). The buffer solution (10% by mass) was then vacuum dried at 60°C for 24 hours to obtain functionalized nanofibers. The nanofibers were composed of hexagonal boron nitride nanofibers and carbon nanofibers in a mass ratio of 1:0.65. The preparation method of imide includes the following steps: The mass ratio of 4,4'-diaminodiphenyl ether, dianhydride, N-methylpyrrolidone, and toluene was 1.8:0.9:30:16. 4,4'-diaminodiphenyl ether and dianhydride were added to N-methylpyrrolidone, and the reaction was carried out under a nitrogen atmosphere at room temperature for 12 hours. After the reaction was complete, toluene was added and stirred thoroughly. The mixture was then refluxed at 180°C for 9 hours. After cooling to room temperature, the mixture was poured into a mixed solution of deionized water and methanol (volume ratio of deionized water to methanol was 1:1). The mass of the water and methanol mixture was twice that of N-methylpyrrolidone. After standing for 1.5 h, the mixture was centrifuged at 5000 rpm for 12 min, the precipitate was collected, and washed three times with deionized water (each time the mass of deionized water was 50% of the mass of N-methylpyrrolidone). Finally, the mixture was vacuum dried at 65 °C for 12 h to obtain the imide. The dianhydride in the imide was composed of a mixture of 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4-hexafluoroisopropylphthalic anhydride in a mass ratio of 0.75:0.45. The specific steps for preparing high-strength and high-toughness seamless oil casing are as follows: S1: Raw materials: By weight percentage, it includes the following components: carbon 0.16%, silicon 0.3%, manganese 0.7%, chromium 11%, molybdenum 3%, aluminum 0.03%, phosphorus 0.007%, zirconium 0.22%, cerium 0.005%, yttrium 0.004%, with the balance being iron and other unavoidable impurities; S2: Preparation of the oil casing substrate: The raw materials from step S1 are steelled in an oxygen-blown converter and fed with Ce wire. The steelmaking temperature is 1600℃, and the mass of Ce wire accounts for 0.03% of the mass of the molten steel. Then, the material is refined outside the ladle (refining temperature is 1620℃, refining time is 50min) and vacuum degassing (vacuum degassing temperature is 1600℃, vacuum degree is 5Pa, vacuum degassing time is 25min, and the argon gas flow rate is 140Nm). 3 The steel is obtained by casting molten steel into a bar-shaped continuous casting billet. The bar-shaped continuous casting billet is heated to 1175℃ in a heating furnace and held for 2 hours. Then, it is pierced at 1100℃ and hot rolled at 920℃. After cooling, a tube blank is obtained. The tube blank is water-cooled and then quenched at 900℃ for 60 minutes. After quenching, it is water-cooled and then subjected to double tempering. The first tempering temperature is 550℃ and the tempering holding time is 30 minutes. The second tempering temperature is 450℃ and the tempering holding time is 120 minutes. After tempering, it is air-cooled to obtain the oil casing base. S3: Pretreatment of the casing substrate: The casing substrate from step S2 is sandblasted. After sandblasting, it is impregnated with a silanized nano-suspension for 1.5 hours (per cm). 2 The oil casing substrate was pretreated by vacuum drying at 110℃ for 2 hours using 0.2 mL of silanized nano suspension. The sandblasting conditions were as follows: 0.4 mm aluminum oxide particles were used for sandblasting, the compressed air pressure was 0.9 MPa, the sandblasting distance was 160 mm, the sandblasting angle was 90°, and the surface roughness was controlled at 100 mm. The preparation method of silanized nano-suspension includes the following steps: The silane coupling agent, a mixed solution of ethanol and deionized water, nanoparticles, and polyvinylpyrrolidone were mixed in a mass ratio of 2:100:0.05:0.05. The silane coupling agent was added to the mixed solution of ethanol and deionized water (volume ratio of ethanol to deionized water was 9:1), and stirred at 2000 rpm for 20 min at room temperature. Then, the nanoparticles were added, and stirring continued for 12 min. Next, polyvinylpyrrolidone was added, and the mixture was stirred until homogeneous. The mixture was then ultrasonically treated for 25 min (ultrasonic power 100 W, ultrasonic frequency 40 kHz) to obtain a silanized nanoparticle suspension. The silane coupling agent was composed of a mixture of 3-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane in a mass ratio of 2:1; the nanoparticles were composed of a mixture of hydroxylated multi-walled carbon nanotubes and nano-silica in a mass ratio of 0.75:0.55. S4: Preparation of high-strength and toughness seamless oil casing: The modified epoxy resin is sprayed onto the surface of the pretreated oil casing substrate in step S3, and then cured. First, it is cured at 120℃ for 1 hour, then at 160℃ for 2 hours, and finally at 200℃ for 3 hours. After curing, a high-strength and toughness seamless oil casing is obtained, wherein the spraying thickness is 250μm. Example 3
[0056] The specific steps for preparing modified epoxy resin are as follows: According to the mass ratio of imide, epoxy resin, functionalized nanofibers, and 4,4'-diaminodiphenylmethane being 0.12:1.1:0.03:0.15, imide was added to epoxy resin, and then stirred at 125°C for 20 min. After cooling to 90°C, functionalized nanofibers were added, and the mixture was stirred at 90°C for 0.5 h. After cooling to 65°C, 4,4'-diaminodiphenylmethane was added, and the mixture was stirred for 20 min. Finally, the mixture was degassed under vacuum at 65°C for 15 min to obtain modified epoxy resin. The preparation method of functionalized nanofibers includes the following steps: Following a mass ratio of nanofibers, Tris buffer solution, dopamine, and N-[3-(trimethoxysilyl)propyl]ethylenediamine of 0.2:160:0.07:0.25, nanofibers were added to 0.01 mol / L Tris buffer solution and sonicated for 25 min (ultrasonic power 100 W, ultrasonic frequency 40 kHz). Dopamine was then added, and sonication was continued for another 25 min (ultrasonic power 100 W, ultrasonic frequency 40 kHz). N-[3-(trimethoxysilyl)propyl]ethylenediamine was then added, and the pH of the system was adjusted to 9 with 0.1 mol / L hydrochloric acid solution. The mixture was stirred for 5.5 h. After the reaction, the mixture was centrifuged at 10000 rpm for 15 min and washed three times each with ethanol and deionized water (each time the ethanol mass was 8% of the Tris buffer solution mass, and each time the deionized water mass was 8% of the Tris buffer solution mass). The buffer solution (10% by mass) was then vacuum dried at 65°C for 24 hours to obtain functionalized nanofibers. The nanofibers were composed of hexagonal boron nitride nanofibers and carbon nanofibers in a mass ratio of 1.1:0.7. The preparation method of imide includes the following steps: The mass ratio of 4,4'-diaminodiphenyl ether, dianhydride, N-methylpyrrolidone, and toluene was 1.9:1:35:17. 4,4'-diaminodiphenyl ether and dianhydride were added to N-methylpyrrolidone, and the mixture was reacted at room temperature under a nitrogen atmosphere for 13 hours. After the reaction was complete, toluene was added and stirred thoroughly. The mixture was then refluxed at 185°C for 8 hours. After cooling to room temperature, the mixture was poured into a mixed solution of deionized water and methanol (volume ratio of deionized water to methanol was 1:1). The mass of the mixed solution of deionized water and methanol was twice that of N-methylpyrrolidone. After standing for 2 hours, the precipitate was collected by centrifugation at 6000 rpm for 10 minutes. The precipitate was washed three times with deionized water (each time the mass of deionized water was 50% of the mass of N-methylpyrrolidone). Finally, it was vacuum dried at 70°C for 12 hours to obtain the imide. The dianhydride was composed of a mixture of 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4-hexafluoroisopropylphthalic anhydride in a mass ratio of 0.8:0.5. The specific steps for preparing high-strength and high-toughness seamless oil casing are as follows: S1: Raw materials: By weight percentage, it includes the following components: carbon 0.18%, silicon 0.4%, manganese 0.8%, chromium 12%, molybdenum 3.5%, aluminum 0.04%, phosphorus 0.01%, zirconium 0.24%, cerium 0.006%, yttrium 0.005%, with the balance being iron and other unavoidable impurities; S2: Preparation of the oil casing substrate: The raw materials from step S1 are steelled in an oxygen-blown converter and fed with Ce wire at a steelmaking temperature of 1650℃. The mass of Ce wire accounts for 0.04% of the mass of the molten steel. The mixture is then refined outside the ladle (refining temperature 1640℃, refining time 40 min) and degassed under vacuum (degassed temperature 1620℃, vacuum degree 6 Pa, degassed time 20 min, argon gas flow rate 160 Nm). 3 The steel is obtained by casting molten steel into a bar-shaped continuous casting billet. The bar-shaped continuous casting billet is heated to 1200℃ in a heating furnace and held for 1.5h. Then, it is pierced at 1120℃ and hot rolled at 940℃. After cooling, a tube blank is obtained. The tube blank is water-cooled and then quenched at 910℃ for 50min. After quenching, it is water-cooled and then double-tempered. The first tempering temperature is 560℃ and the tempering holding time is 25min. The second tempering temperature is 460℃ and the tempering holding time is 110min. After tempering, it is air-cooled to obtain the oil casing base. S3: Pretreatment of the casing substrate: The casing substrate from step S2 is sandblasted. After sandblasting, it is impregnated with a silanized nano-suspension for 2 hours (per cm). 2The oil casing substrate was pretreated by vacuum drying at 115℃ for 1.5h using 0.3mL silanized nano suspension. The sandblasting conditions were as follows: 0.4mm aluminum oxide particles were used for sandblasting, the compressed air pressure was 1MPa, the sandblasting distance was 180mm, the sandblasting angle was 90°, and the surface roughness was controlled at 110mm. The preparation method of silanized nano-suspension includes the following steps: The silane coupling agent, a mixed solution of ethanol and deionized water, nanoparticles, and polyvinylpyrrolidone were mixed in a mass ratio of 2.2:110:0.06:0.06. The silane coupling agent was added to the mixed solution of ethanol and deionized water (volume ratio of ethanol to deionized water was 9:1), and stirred at 2000 rpm for 25 min at room temperature. Then, the nanoparticles were added, and stirring continued for 15 min. Next, polyvinylpyrrolidone was added, and the mixture was stirred until homogeneous. The mixture was then ultrasonically treated for 30 min (ultrasonic power 100 W, ultrasonic frequency 40 kHz) to obtain a silanized nanoparticle suspension. The silane coupling agent was composed of a mixture of 3-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane in a mass ratio of 2:1; the nanoparticles were composed of a mixture of hydroxylated multi-walled carbon nanotubes and nano-silica in a mass ratio of 0.8:0.6. S4: Preparation of high-strength and toughness seamless oil casing: Modified epoxy resin is sprayed onto the surface of the pretreated oil casing substrate in step S3, and then cured. First, it is cured at 125℃ for 0.5h, then at 165℃ for 1.5h, and finally at 205℃ for 2.5h. After curing, a high-strength and toughness seamless oil casing is obtained, wherein the spraying thickness is 300μm.
[0057] Comparative Example 1 The difference between this comparative example and Example 3 is that, in the preparation of the modified epoxy resin, the nanofibers were replaced with hexagonal boron nitride nanofibers of equal mass, while the remaining steps and raw materials were the same as in Example 3. The preparation method of functionalized nanofibers includes the following steps: Hexagonal boron nitride nanofibers, Tris buffer solution, dopamine, and N-[3-(trimethoxysilyl)propyl]ethylenediamine were added to 0.01 mol / L Tris buffer solution in a mass ratio of 0.2:160:0.07:0.25. The mixture was ultrasonically treated for 25 min (100 W, 40 kHz), followed by the addition of dopamine and another 25 min of ultrasonic treatment (100 W, 40 kHz). Then, N-[3-(trimethoxysilyl)propyl]ethylenediamine was added, and the pH was adjusted to 9 with 0.1 mol / L hydrochloric acid solution. The mixture was stirred for 5.5 h. After the reaction, the mixture was centrifuged at 10,000 rpm for 15 min and washed three times each with ethanol and deionized water (each time the ethanol mass was 8% of the Tris buffer solution mass, and each time the deionized water mass was 8% of the Tris buffer solution mass). The buffer solution was 10% by mass, and finally vacuum dried at 65℃ for 24 h to obtain functionalized nanofibers.
[0058] Comparative Example 2 The difference between this comparative example and Example 3 is that, in the preparation of the modified epoxy resin, the nanofibers were replaced with carbon nanofibers of equal mass, while the remaining steps and raw materials were the same as in Example 3. The preparation method of functionalized nanofibers includes the following steps: The carbon nanofibers, Tris buffer solution, dopamine, and N-[3-(trimethoxysilyl)propyl]ethylenediamine were mixed in a mass ratio of 0.2:160:0.07:0.25. The mixture was added to 0.01 mol / L Tris buffer solution and sonicated for 25 min (100 W, 40 kHz). Dopamine was then added, and the mixture was sonicated for another 25 min (100 W, 40 kHz). N-[3-(trimethoxysilyl)propyl]ethylenediamine was then added, and the pH was adjusted to 9 with 0.1 mol / L hydrochloric acid solution. The mixture was stirred for 5.5 h. After the reaction, the mixture was centrifuged at 10,000 rpm for 15 min and washed three times each with ethanol and deionized water (each time the ethanol mass was 8% of the Tris buffer solution mass, and each time the deionized water mass was 10% of the Tris buffer solution mass). Finally, the mixture was vacuum dried at 65 °C for 24 h to obtain the functionalized nanofibers.
[0059] Comparative Example 3 The difference between this comparative example and Example 3 is that, in the preparation of the modified epoxy resin, the dianhydride was replaced by 1,4,5,8-naphthalenetetracarboxylic anhydride by an equal mass, while the remaining steps and raw materials were the same as in Example 3. The preparation method of imide includes the following steps: The mass ratio of 4,4'-diaminodiphenyl ether, 1,4,5,8-naphthalenetetracarboxylic anhydride, N-methylpyrrolidone, and toluene was 1.9:1:35:17. 4,4'-diaminodiphenyl ether and 1,4,5,8-naphthalenetetracarboxylic anhydride were added to N-methylpyrrolidone and reacted at room temperature under a nitrogen atmosphere for 13 hours. After the reaction was complete, toluene was added and stirred until homogeneous. The mixture was then refluxed at 185°C for 8 hours. After cooling to room temperature, the mixture was poured into a mixture of deionized water and methanol (volume ratio of deionized water to methanol was 1:1) (the mass of the deionized water and methanol mixture was twice the mass of N-methylpyrrolidone). The mixture was allowed to stand for 2 hours, and the precipitate was collected by centrifugation at 6000 rpm for 10 minutes. The precipitate was washed three times with deionized water (each time the mass of deionized water was 50% of the mass of N-methylpyrrolidone). Finally, the precipitate was vacuum dried at 70°C for 12 hours to obtain the imide.
[0060] Comparative Example 4 The difference between this comparative example and Example 3 is that, in the preparation of the modified epoxy resin, the dianhydride was replaced by an equal mass of 4,4-hexafluoroisopropylphthalic anhydride, while the remaining steps and raw materials were the same as in Example 3. The preparation method of imide includes the following steps: The mass ratio of 4,4'-diaminodiphenyl ether, 4,4-hexafluoroisopropylphthalic anhydride, N-methylpyrrolidone, and toluene was 1.9:1:35:17. 4,4'-diaminodiphenyl ether and 4,4-hexafluoroisopropylphthalic anhydride were added to N-methylpyrrolidone and reacted at room temperature under a nitrogen atmosphere for 13 hours. After the reaction was complete, toluene was added and stirred until homogeneous. The mixture was then refluxed at 185°C for 8 hours. After cooling to room temperature, the mixture was poured into a mixture of deionized water and methanol (volume ratio of deionized water to methanol was 1:1) (the mass of the deionized water and methanol mixture was twice the mass of N-methylpyrrolidone). The mixture was allowed to stand for 2 hours, and the precipitate was collected by centrifugation at 6000 rpm for 10 minutes. The precipitate was washed three times with deionized water (each time the mass of deionized water was 50% of the mass of N-methylpyrrolidone). Finally, the precipitate was vacuum dried at 70°C for 12 hours to obtain the imide.
[0061] Comparative Example 5 The difference between this comparative example and Example 3 is that, in the preparation of high-strength and tough seamless oil casing, the tube blank is quenched and tempered in step S2, while the remaining steps and raw materials are the same as in Example 3. S2: Preparation of the oil casing substrate: The raw materials from step S1 are steelled in an oxygen-blown converter and fed with Ce wire at a steelmaking temperature of 1650℃. The mass of Ce wire accounts for 0.04% of the mass of the molten steel. The mixture is then refined outside the ladle (refining temperature 1640℃, refining time 40 min) and degassed under vacuum (degassed temperature 1620℃, vacuum degree 6 Pa, degassed time 20 min, argon gas flow rate 160 Nm). 3 The steel is obtained by casting molten steel into a bar-shaped continuous casting billet. The bar-shaped continuous casting billet is heated to 1200℃ in a heating furnace and held for 1.5h. Then, it is pierced at 1120℃ and hot-rolled at 940℃. After cooling, a tube blank is obtained. The tube blank is water-cooled and then quenched at 910℃ for 50min. After quenching, it is water-cooled and then subjected to single tempering at 560℃ for 25min. After tempering, it is air-cooled to obtain the oil casing base.
[0062] Comparative Example 6 The difference between this comparative example and Example 3 is that, in the preparation of high-strength and tough seamless oil casing, in step S3, nanoparticles are replaced with hydroxylated multi-walled carbon nanotubes of equal mass, while the remaining steps and raw materials are the same as in Example 3. The preparation method of silanized nano-suspension includes the following steps: The silane coupling agent, a mixed solution of ethanol and deionized water, hydroxylated multi-walled carbon nanotubes, and polyvinylpyrrolidone were mixed in a mass ratio of 2.2:110:0.06:0.06. The silane coupling agent was added to the mixed solution of ethanol and deionized water (volume ratio of ethanol to deionized water was 9:1), and stirred at 2000 rpm for 25 min at room temperature. Then, hydroxylated multi-walled carbon nanotubes were added, and stirring was continued for 15 min. Polyvinylpyrrolidone was then added, and the mixture was stirred evenly and then sonicated for 30 min (ultrasonic power of 100 W and ultrasonic frequency of 40 kHz) to obtain a silanized nano-suspension. The silane coupling agent was composed of 3-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane mixed in a mass ratio of 2:1.
[0063] Comparative Example 7 The difference between this comparative example and Example 3 is that, in the preparation of high-strength and tough seamless oil casing, in step S3, nanoparticles are replaced with nano-silica of equal mass, while the remaining steps and raw materials are the same as in Example 3. The preparation method of silanized nano-suspension includes the following steps: The silane coupling agent, a mixed solution of ethanol and deionized water, nano-silica, and polyvinylpyrrolidone were mixed in a mass ratio of 2.2:110:0.06:0.06. The silane coupling agent was added to the mixed solution of ethanol and deionized water (volume ratio of ethanol to deionized water was 9:1), and stirred at 2000 rpm for 25 min at room temperature. Then, nano-silica was added, and stirring was continued for 15 min. Polyvinylpyrrolidone was then added, and the mixture was stirred evenly. After stirring, the mixture was ultrasonically treated for 30 min (ultrasonic power was 100 W, ultrasonic frequency was 40 kHz) to obtain a silanized nano-suspension. The silane coupling agent was composed of 3-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane mixed in a mass ratio of 2:1.
[0064] Comparative Example 8 The difference between this comparative example and Example 3 is that, in the preparation of high-strength and tough seamless oil casing, in step S3, the oil casing substrate in step S2 is only sandblasted, while the remaining steps and raw materials are the same as in Example 3. S3: Pre-treatment of the oil casing substrate: The oil casing substrate in step S2 is subjected to sandblasting. After sandblasting, a pre-treated oil casing substrate is obtained. The sandblasting conditions are as follows: 0.4 mm diameter aluminum oxide particles are used for sandblasting, the compressed air pressure is 1 MPa, the sandblasting distance is 180 mm, the sandblasting angle is 90°, and the surface roughness is controlled at 110 mm.
[0065] Comparative Example 9 The difference between this comparative example and Example 3 is that, in the preparation of high-strength and tough seamless oil casing, the modified epoxy resin in step S4 is obtained by functionalized nanofiber modified epoxy resin, while the remaining steps and raw materials are the same as in Example 3. The specific steps for preparing modified epoxy resin are as follows: The functionalized nanofibers were added to the epoxy resin in a mass ratio of 1.1:0.03:0.15, and then stirred at 90°C for 0.5 h. After cooling to 65°C, 4,4'-diaminodiphenylmethane was added and stirred for 20 min. Finally, the mixture was degassed under vacuum at 65°C for 15 min to obtain the modified epoxy resin.
[0066] Comparative Example 10 The difference between this comparative example and Example 3 is that, in the preparation of high-strength and tough seamless oil casing, the modified epoxy resin in step S4 is obtained by imide-modified epoxy resin, while the remaining steps and raw materials are the same as in Example 3. The specific steps for preparing modified epoxy resin are as follows: The modified epoxy resin was prepared by adding imide, epoxy resin, and 4,4'-diaminodiphenylmethane in a mass ratio of 0.12:1.1:0.15. The mixture was stirred at 125°C for 20 min, cooled to 65°C, and then 4,4'-diaminodiphenylmethane was added and stirred for another 20 min. Finally, the mixture was degassed under vacuum at 65°C for 15 min to obtain the modified epoxy resin.
[0067] The high-strength and high-toughness seamless oil casings prepared in Examples 1-3 and Comparative Examples 1-10 were subjected to mechanical property, corrosion resistance, and adhesion tests. Mechanical property tests: The yield strength, tensile strength, and elongation of the high-strength and high-toughness seamless oil casings prepared in Examples 1-3 and Comparative Examples 1-10 were tested according to API 5CT (10th Edition). Corrosion resistance tests: The coatings were tested for 90 days against 10% H2SO4 solution and 10% NaOH solution according to GB / T 9274-1988 "Determination of Resistance to Liquid Media for Paints and Varnishes". The coatings were tested for 90 days against neutral salt spray according to GB / T 1771-2007 "Determination of Resistance to Neutral Salt Spray for Paints and Varnishes". The coating adhesion was tested according to GB / T 9286-2021 "Cross-cut Test for Paints and Varnishes". The test results are shown in Table 1 below. Table 1 Performance parameters of high-strength and high-toughness seamless oil casings obtained in Examples 1-3 and Comparative Examples 1-10
[0068] As shown in Table 1 above, comparing Comparative Examples 1-4 and Example 3, the test results of the high-strength and tough seamless oil casing prepared by replacing the nanofibers with hexagonal boron nitride nanofibers or carbon nanofibers, or replacing the dianhydrides with 1,4,5,8-naphthalenetetracarboxylic anhydride or 4,4-hexafluoroisopropylphthalic anhydride, are worse than those of Example 3. This indicates that the nanofibers composed of hexagonal boron nitride nanofibers and carbon nanofibers have a synergistic effect, which can effectively improve the corrosion resistance, thermal stability, mechanical strength, and toughness of epoxy resin. The dianhydride composed of 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4-hexafluoroisopropylphthalic anhydride can form an imide with diamine. When added to epoxy resin, it can play a synergistic role, which can better improve the corrosion resistance of epoxy resin, effectively improve the mechanical properties and thermal stability of seamless oil casing, and have a good influence on the adhesion of coating. Comparing Comparative Examples 5-8 and Example 3, it can be seen that in step S2, quenching and single tempering of the tube blank, or in step S3, replacing the nanoparticles with hydroxylated multi-walled carbon nanotubes or nano-silica, or in step S3, only sandblasting the oil casing substrate in step S2, the test results of the high-strength and toughness seamless oil casing are worse than those of Example 3. This indicates that quenching and double tempering of the tube blank can effectively reduce the grain size and significantly improve the toughness and mechanical strength of the seamless oil casing. The nanoparticles, composed of hydroxylated multi-walled carbon nanotubes and nano-silica, not only improve the mechanical properties and corrosion resistance of the seamless oil casing, but also enhance the adhesion between the coating and the oil casing substrate. Furthermore, sandblasting the oil casing substrate in step S2 followed by treatment with a silanized nano-suspension effectively improves the adhesion between the oil casing substrate and the coating, and also has a positive impact on the mechanical properties and corrosion resistance of the seamless oil casing. Comparing Comparative Examples 9-10 and Example 3, it can be seen that in step S4, the modified epoxy resin is prepared by functionalized nanofibers or by imide-modified epoxy resin. The test results of the high-strength and tough seamless oil casing are worse than those of Example 3. This indicates that by modifying the epoxy resin with both imide and functionalized nanofibers, a better modified epoxy resin can be formed, which further improves the mechanical strength, toughness, corrosion resistance, and thermal stability of the seamless oil casing, and increases the adhesion between the coating and the oil casing substrate.
[0069] As shown in Table 1 above, the high-strength and high-toughness seamless oil casings prepared in Examples 1-3, compared to those prepared in Comparative Examples 1-10, achieved high-strength and high-toughness seamless oil casings by first treating the oil casing substrate with a silanized suspension, then spraying modified epoxy resin, and finally curing it. This demonstrates that the high-strength and high-toughness seamless oil casings prepared in this invention not only possess good mechanical strength, toughness, corrosion resistance, and thermal stability, but also exhibit good adhesion between the coating and the oil casing substrate, extending the service life of the seamless oil casing and resulting in superior overall performance.
[0070] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0071] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined by the present invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-strength and high-toughness seamless oil casing, characterized in that, Includes the following steps: S1: Raw materials: By weight percentage, it includes the following components: carbon 0.12-0.18%, silicon 0.2-0.4%, manganese 0.6-0.8%, chromium 10-12%, molybdenum 2.5-3.5%, aluminum 0.02-0.04%, phosphorus 0.005-0.01%, zirconium 0.2-0.24%, cerium 0.004-0.006%, yttrium 0.003-0.005%, with the balance being iron and other unavoidable impurities; S2: Preparation of oil casing substrate: The raw materials in step S1 are melted to obtain molten steel. The molten steel is cast into a rod-shaped continuous casting billet, and then pierced and hot rolled to obtain a tube blank. The tube blank is quenched and double tempered to obtain the oil casing substrate. S3: Pre-treatment of the oil casing substrate: The oil casing substrate in step S2 is treated with a silanized nano suspension to obtain a pre-treated oil casing substrate; S4: Preparation of high-strength and toughness seamless oil casing: The modified epoxy resin is sprayed onto the surface of the pretreated oil casing substrate in step S3, and then cured to obtain a high-strength and toughness seamless oil casing. The modified epoxy resin is prepared by functionalizing nanofibers and imide-modified epoxy resin.
2. The method for preparing a high-strength and high-toughness seamless oil casing according to claim 1, characterized in that, In step S2, the double tempering process is as follows: after quenching, water cooling is performed, followed by double tempering. The first tempering temperature is 540-560℃, and the tempering holding time is 25-35min. The second tempering temperature is 440-460℃, and the tempering holding time is 110-130min. After tempering, air cooling is performed to obtain the oil casing substrate.
3. The method for preparing a high-strength and high-toughness seamless oil casing according to claim 1, characterized in that, In step S3, the preparation method of the silanized nano-suspension includes the following steps: Add the silane coupling agent to a mixed solution of ethanol and deionized water and stir for 15-25 minutes. Then add the nanoparticles and continue stirring. Add the dispersant, stir until homogeneous, and then sonicate to obtain a silanized nano suspension.
4. The method for preparing a high-strength and high-toughness seamless oil casing according to claim 3, characterized in that, The nanoparticles are composed of hydroxylated multi-walled carbon nanotubes and nano-silica in a mass ratio of 0.7-0.8:0.5-0.
6.
5. The method for preparing a high-strength and high-toughness seamless oil casing according to claim 1, characterized in that, The preparation method of the modified epoxy resin includes the following steps: Imide is added to epoxy resin, and then stirred at 115-125℃ for 20-30 minutes. After cooling, functionalized nanofibers are added and stirred. After cooling, curing agent is added and stirred evenly. Finally, vacuum degassing is performed to obtain modified epoxy resin.
6. The method for preparing a high-strength and high-toughness seamless oil casing according to claim 5, characterized in that, The preparation method of the functionalized nanofibers includes the following steps: Nanofibers were added to Tris buffer solution and sonicated. Dopamine was then added, and sonication was continued. N-[3-(trimethoxysilyl)propyl]ethylenediamine was then added, and hydrochloric acid solution was added to adjust the pH of the system to 8-9. The mixture was stirred for 4.5-5.5 h. After the reaction was completed, the nanofibers were centrifuged, washed with ethanol and deionized water, and finally vacuum dried to obtain functionalized nanofibers.
7. The method for preparing a high-strength and high-toughness seamless oil casing according to claim 6, characterized in that, The nanofibers are composed of hexagonal boron nitride nanofibers and carbon nanofibers in a mass ratio of 0.9-1.1:0.6-0.
7.
8. The method for preparing a high-strength and high-toughness seamless oil casing according to claim 5, characterized in that, The method for preparing the imide includes the following steps: Diamine and dianhydride were added to N-methylpyrrolidone and reacted under a nitrogen atmosphere for 11-13 hours. After the reaction was completed, toluene was added and stirred until homogeneous. The mixture was then refluxed and cooled to room temperature. The solution was then poured into a mixture of deionized water and methanol, allowed to stand, centrifuged, washed with deionized water, and finally dried under vacuum to obtain imide.
9. The method for preparing a high-strength and high-toughness seamless oil casing according to claim 8, characterized in that, The dianhydride is composed of 1,4,5,8-naphthalenetetracarboxylic anhydride and 4,4-hexafluoroisopropylphthalic anhydride in a mass ratio of 0.7-0.8:0.4-0.
5.
10. A high-strength and high-toughness seamless oil casing prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
High-temperature-resistant fireproof coating powder and preparation method thereof
CN120118590A
Preparation method of composite modified epoxy resin
CN120230377A
Method for Applying an Anti-Corrosion Coating on Parts of a Duct Including the Use of a Silane Aqueous Solution and an Epoxy Powdery Paint
US20100055327A1
Steel for hydrogen sulfide stress corrosion cracking resistant martensitic stainless steel oil casing pipe, and oil casing pipe and production method therefor
WO2017162160A1